(untitled) (Theatrum historiae, 2023)
The study of tax sources for the 17th and 18th centuries is not sufficiently developed in Czech or foreign research. Czech historiography has focused most extensively on a trio of cadastres, which were used to address various questions relating to social and economic history. However, the way in which taxes were distributed among individual taxpayers in the second half of the 17th century and throughout the 18th century has not been studied. This study attempts to answer this situation by using the example of royal towns, where (in contrast to the environment of the landed estates) the functional system remained essentially medieval in origin. The cadastres prescribed tax only at the level of individual localities, not taxpayers. To this end, the amount prescribed was apportioned to the urban population by means of a system (šacuňky) which took account of the property situation of the individual taxpayers. This distribution was recorded in the books of subrepartitions. The payment capacity itself was then recorded (as in rural areas) in the so-called contribution books, where the tax official recorded the tax paid in addition to the payment obligation.